2018
DOI: 10.1002/jez.2238
|View full text |Cite
|
Sign up to set email alerts
|

Light at night affects hippocampal and nidopallial cytoarchitecture: Implication for impairment of brain function in diurnal corvids

Abstract: Our previous studies have shown that light at night (LAN) impaired cognitive performance and affected neurogenesis and neurochemistry in the cognition‐associated brain regions, particularly the hippocampus (HP) and lateral caudal nidopallium (NCL) of Indian house crows (Corvus splendens). Here, we examined the cytoarchitecture and mapped out the morphology of neurons and glia–neuron density in HP and NCL regions of crows that were first entrained to 12‐hr light (LL): 12‐hr darkness (LD) and then exposed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…This is because HC responded to ALAN differently than MSt and NC, both in the short-term [ 8 ], as well as in the long-term ALAN exposures (our present study). In the short-term (3 weeks), neuronal densities decreased in both the MSt and the NC, whereas no significant change was observed in the HC, similar to what had been found when Indian house crows were exposed to an even shorter ALAN duration (two weeks) [ 4 ]. However, in the long-term exposure of our current study (seven weeks), total neuronal densities in the HC increased compared to controls, whereas no changes were observed in MSt and NC.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This is because HC responded to ALAN differently than MSt and NC, both in the short-term [ 8 ], as well as in the long-term ALAN exposures (our present study). In the short-term (3 weeks), neuronal densities decreased in both the MSt and the NC, whereas no significant change was observed in the HC, similar to what had been found when Indian house crows were exposed to an even shorter ALAN duration (two weeks) [ 4 ]. However, in the long-term exposure of our current study (seven weeks), total neuronal densities in the HC increased compared to controls, whereas no changes were observed in MSt and NC.…”
Section: Discussionsupporting
confidence: 65%
“…Despite a growing number of studies that demonstrate adverse effects of artificial light at night (ALAN) on the behaviour and physiology of many species (e.g., reviewed in [ 1 , 2 ]), still, in birds relatively little is known regarding its effects on brain plasticity. The few existing studies report a decrease in the numbers of newly formed neurons in the hippocampus (HC) of Indian house crows ( Corvus splendens ) [ 3 ], and a decrease in soma size of neurons in the HC and the lateral caudal nidopallium (NCL) in this species, suggesting reduced neuronal plasticity [ 4 ]. We have also studied the effect of ALAN on neuronal plasticity in another diurnal species, zebra finches ( Taeniopygia guttata ), which have excellent visual abilities [ 5 ] and their physiology, reproduction and survival are greatly affected by circadian and circannual rhythms [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular and neuroanatomical mechanisms of cognitive impairment associated with dLAN exposure remain mostly unsolved. However, Taufique et al [ 56 ] reported significant decrease in the neuroplasticity through the reduction of soma size and decreased number of glial cells in the hippocampus of Indian house crows exposed to dLAN. In the current study, we have also observed disruption and increased pyknosis and chromatolysis (characteristics of damaged neurons) in the hippocampal and cerebral cortex neurons of the dLAN exposed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on crows also demonstrated the negative impact of LL and dLAN on brain architecture. LL and dLAN decreased neuronal soma size and glial numbers in the hippocampus and lateral caudal nidopallium [42]. Neuronal soma size and glia-neuron ratios are important for optimal brain functions [42][43][44].…”
Section: Adverse Effects On Cognitive Functionsmentioning
confidence: 95%